Routing algorithm for railway monitoring linear WSN based on improved PSO - Cuiran LI; Xuejie WANG; Jianli XIE; Anqi LYU (Tongxin xuebao)
To solve the problems of short network lifetime and large data transmission delay, caused by unbalanced node energy consumption of linear wireless sensor network in railway monitoring scenario, a routing algorithm based on particle swarm optimization theory and breadth first search was proposed.The fitness function was constructed based on the relative energy consumption, spacing and load of candidate cluster heads.The local search ability of particle swarm algorithm was enhanced by adjusting the inertia weight coefficient to set up the cluster head optimal set.Meanwhile, a path cost function driven by energy consumption and delay was built up, and the optimal main path from the source node to the sink node was obtained by breadth first search.Lastly, a Q-learning alternative path updating and route maintenance mechanism based on discrete Markov decision process (MDP) was designed.Simulation results show that the proposed algorithm can balance the node energy consumption effectively, and has also advantages in prolonging the network lifetime and reducing the data transmission delay.